Integrating AISAS and TAM to Explain Conversion Drop-Off in Short-Video Marketing - Ghina Taffana Teja Putri (International Journal of Science and Environment (IJSE), 2026)
Short-video platforms such as TikTok have demonstrated exceptional capacity to generate audience engagement; however, translating such engagement into measurable conversion outcomes remains a persistent challenge. This study investigates the engagement–conversion gap by integrating the AISAS (Attention–Interest–Search–Action–Share) framework with the Technology Acceptance Model (TAM) to explain user drop-off in short-video marketing funnels. Adopting an explanatory mixed-methods design, this research draws on TikTok analytics, website traffic data, booking records, survey responses, and internal interviews from a service-based business in Indonesia. The findings indicate that TikTok content successfully generates Attention and Interest but exhibits limited progression to Search and Action stages. Although users report high perceived usefulness, entertainment value, and booking intention, inconsistent call-to-action (CTA) execution and cross-platform friction significantly constrain conversion outcomes. By integrating AISAS and TAM, this study contributes a multi-level explanation of conversion drop-off that combines perceptual, behavioral, and structural dimensions. The findings highlight that engagement intensity alone is insufficient for conversion and underscore the importance of funnel continuity in short-video marketing.